Captiver/séduire. Note sur la gestuelle des joueurs de hautbois nāgasvaram - William Tallotte (Transposition)
Playing the nāgasvaram shawm involves gestures that are not directly involved in sound production: the instrument is indeed regularly set in motion, vertically, horizontally, or by combining these two planes. Musicians do not generally speak of these gestures and the movements they imply, but they suggest, sometimes, that their function is to gain the attention of the auditors/spectators, and even to seduce them. This article, from fieldwork carried out in Tamil Nadu, looks into the codes that underlie these gestures and the role, even the meaning, which we can reasonably grant them in various performance situations.